Guru sebagai sarana penguatan pendidikan karakter peserta didik - akmal, moch syarifuddin (Maliki Interdisciplinary Journal, 2024)
An Practicing character education is one way to build moral education. The purpose of this writing is to study and analyze teacher example in implementing character education in schools. This article is the result of an analysis studying the literature on the topic discussed. Literature studies or literature reviews are used as models. The results obtained from the research show that implementing character education in schools is the responsibility of all school children, but teachers have an important role in implementing the program. Therefore, it can be concluded that the success of character education in schools depends on how much teachers can be role models for their students, so of course we also need teachers to create students with character.